Gender Differences in Response to Cold Pressor Test in the Age Group of 18-30 Years (International Journal of Physiology, 2020)
Introduction: The Cold Pressor Test (CPT) was first introduced by Hines and Brown in 1932. It wasdesigned to measure the reactivity of the blood vessels to a standard stimulus2 . Cold Pressor Test is anestablished challenge test of sympathetic vascular regulation. Sympathetic nervous system activity varies inmales and females.Aim: To study the response of Cold Pressor Test on blood pressure in normal healthy young adult malesand females.Materials and Method: After Institutional ethics committee approval, a total of 104 subjects in the agegroup of 18-30 years were recruited with informed consent for the study, after considering inclusion andexclusion criteria. Subjects were explained about the test procedure. Basal blood pressure (pre-test BP)was recorded after 20 min. of rest. Systolic and diastolic blood pressure was measured in mmHg (pre-test).Subject was asked to dip left hand till the wrist in cold water (40-80 C) for 1 min. (minute).Blood pressurewas recorded from right arm during the test, 1 minute, 2 minutes, 3 minutes and 4 minutes after the test.Result: Basal BP was significantly higher in males than in females. Systolic BP(SBP) response, DiastolicBP response (DBP) to CPT were statistically higher in males compared to females.Conclusions: The gender variations are seen due to differences in the sympathetic nervous system activityand due to the effect of sex hormones. Males are more prone to develop hypertension and other cardiovasculardisorders when compared to females due to higher sympathetic activity.